Secular trends in motor performance in Swiss children and adolescents from 1983 to 2018 - Knaier, Elisa; Chaouch, Aziz; Caflisch, Jon A.; Rousson, Valentin; Wehrle, Flavia M.; Kakebeeke, Tanja H.; Jenni, Oskar G. (Frontiers in Public Health, 2023)
Environmental changes, including globalization, urbanization, social and cultural changes in society, and exposure to modern digital technology undoubtedly have an impact on children’s activity and lifestyle behavior. In fact, marked reductions in children’s physical activity levels have been reported over the years and sedentary behavior has increased around the world. The question arises whether these environmental changes had an impact on general motor performance in children and adolescents? The study aimed to investigate secular trends of motor performance in Swiss children and adolescents, aged between 7 and 18 years, over a period of 35 years from 1983 to 2018. Longitudinal data on the five motor components of the Zurich Neuromotor Assessment (ZNA) – pure motor (PM), fine motor (FM), dynamic balance (DB), static balance (SB), and contralateral associated movements (CAM) – were pooled with cross-sectional data on PM and FM from eight ZNA studies between 1983 and 2018. Regression models were used to estimate the effect of year of birth on motor performance and body mass index (BMI) measurements. Models were adjusted for age, sex, and socioeconomic status. The secular trend estimates in standard deviation scores (SDS) per 10 years were -0.06 [-0.33; 0.22, 95% Confidence Interval] for PM, -0.11 [-0.41; 0.20] for FM, -0.38 [-0.66; -0.09] for DB (-0.42 when controlled for BMI), -0.21 [-0.47; 0.06] for SB, and -0.01 [-0.32; 0.31] for CAM. The mean change in BMI data was positive with 0.30 SDS [0.07; 0.53] over 10 years. Despite substantial societal changes since the 1980s, motor performance has remained relatively stable across generations. No secular trend was found in FM, PM, SB, and CAM over a period of 35 years. A secular trend in DB was present independent of the secular trend in body mass index.